A Randomized Thorough QT Study of Apomorphine Sublingual Film in Patients With Parkinson's Disease. Issue 9 (28th July 2022) - Stocchi, Fabrizio; Peckham, Elizabeth L.; De Pandis, Maria Francesca; Sciarappa, Ken; Kleiman, Robert; Agbo, Felix; Olanow, C. Warren; Blum, David; Navia, Bradford
Abstract: A randomized thorough QT study was conducted to assess the effects of apomorphine sublingual film (SL‐APO) on corrected QT interval (QTc) and other cardiac conduction parameters in patients with Parkinson's disease (PD) and "OFF" episodes. Patients were titrated to an SL‐APO dose that resulted in FULL "ON, " followed by up to two additional doses (maximum 60 mg), then randomized at the highest tolerated dose to a treatment sequence of SL‐APO, placebo, and moxifloxacin (400 mg, positive control) in a three‐way crossover design. Changes from baseline in time‐matched, placebo‐adjusted Fridericia‐corrected QTc interval (ΔΔQTcF) and Bazett‐corrected QTc interval (ΔΔQTcB) were analyzed from postdose electrocardiograms. Forty patients were randomized and received single doses of study treatments. Upper limits of 90% confidence intervals (CIs) for ΔΔQTcF of SL‐APO were below the 10‐millisecond regulatory threshold at all prespecified timepoints, demonstrating no clinically significant effect on QTcF. Lower limits of 90% CIs for ΔΔQTcF of moxifloxacin exceeded the 5‐millisecond regulatory threshold at all timepoints up to 3 hours, confirming assay sensitivity. SL‐APO had no clinically meaningful effects on QTcB, PR/QRS intervals, heart rate, or electrocardiogram‐derived morphology (EudraCT identifier: 2016‐001762‐29; ClinicalTrials.gov identifier: NCT03187301).